Research algorithms for emergency medicine. - Looney, G L; Roy, A; Anderson, G V; Scharf, R F (Annals of Emergency Medicine, 1980)
The computer-instigated development of graphic depictions showing rationales and decisions required in the care of patients has allowed clinicians to standardize science in the art of clinical medicine. Such condensation of medical judgment and information into algorithms is particularly important for emergency medicine. This paper describes the background and development of such algorithms in a research setting, and suggests modes for adaptation to clinical settings.